IMPLEMENTATION OF REGENT REGULATION (PERBUB) No. 18 of 2011 CONCERNING THE DESCRIPTION OF STRUCTURAL POSITION AND WORKING PROCEDURE OF KESBANGPOL (Office of National Unity and Politics) - adminjfh, adminjfh; Mila, Sitta Saraya (Journal Legal Dialectics, 2022)
The office of national unity and politics of kendal district is a body formed to implement the provisions of article 44 of kendal district regulation number 18 of 2011 concerning the organization and working procedures of the regional development planing agency, inspectirtae, and tehnical institutions of kendal district, in order to be more effective and succesful in order to determine the description of structural and work title tasks in the office of national unity and politics of kendal district. Each district must have a problem of a awarenenss of national unity and politics in kendal district in this case the regent of kendal district willnot be able to handle it alone, then the fuction of the office of national unity and politics kendal district not only helps the regent of kendal in terms of national unity and politics but also participates in formulating technical policies in the field of national unity,politics and for development in the field of ideology.This research is a field research wit qualitative approach that is descriptive analysis. Data sources include; primary data, obtained through online interviews with designated sources, as well as secondary data, inthe form of regent kendal regulations, books, internet,and official documents related to research.The results showed that the kendal district police office has structures, procedures and duties related to regional tehnical problems in the kendal district that have been implemeted in accordance with the regulation of the regent of kendal number 18 of 2011. The obstacle faced is the socialization of kendal regent regulation number 18 of 2011 which is poorly understood by residents of kendal district. Efforts made to overcome these of constraints are changing the strategy to expand the scope of the region and optimize each activity in order to achieve the objectives of the activities carried out kesbangpol kendal district.